The Legal Position of Notary Covernote on Credit Agreement When Bad Credit Occurs - Adi Yusman; Widhi Handoko; Rakhmat Bowo Suharto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The purpose of this study is to analyze: 1) The legal position of a notary covernote in a credit agreement in the event of bad credit at Bank Rakyat Indonesia Pangkal Pinang. 2). The process of settling bad loans in a credit agreement based on a notary covernote at Bank Rakyat Indonesia Pangkal Pinang. The approach method used in this study is an empirical juridical approach. The research specification used is descriptive analytical research. This type of data uses primary data and secondary data with library research and interview collection methods. The data analysis method used in this research is descriptive analysis. The results of the study concluded: 1) The legal position of a notary covernote in a credit agreement in the event of bad credit at Bank Rakyat Indonesia Pangkal Pinang is that the covernote is used as the basis for credit disbursement. Notary covernotes should not be used as the basis for credit disbursement, because basically covernotes are only temporary guarantees. A covernote made by a notary is usually only a statement that the certification process is still ongoing. Covernote does not have a legal umbrella because it is not regulated in laws and regulations, both the Banking Law and UUJN, so that the consequences that will then be caused by the existence of this covernote apply legal provisions both criminally and civilly. 2). The process of settling bad loans in a credit agreement based on a notary covernote at Bank Rakyat Indonesia Pangkal Pinang is completed through litigation/lawsuits to court. Notary G was proven to have committed a criminal act of corruption together and was detrimental to the state. In the decision of the Notary Court, they must be criminally responsible and fined. The use of a notary covernote in a credit agreement is basically not prohibited and is possible under the Banking Law and the Mortgage Law. In the event of non-performing loans before the issuance of mortgage rights, the bank only serves as a concurrent creditor. Legal protection for banks is based on Articles 1131 and 1132 of the Civil Code. In the event of non-performing loans before the issuance of mortgage rights, the bank only serves as a concurrent creditor. Legal protection for banks is based on Articles 1131 and 1132 of the Civil Code.